Stunting prevention efforts through knowledge interventions of toddler mothers using booklets and video - Dali Dali; Nurjannah Nurjannah; Dyah Noviawati Setya Arum; Taamu Taamu; Siti Khuzaiyah (Jurnal Kesehatan Ibu dan Anak, 2022)
One of the efforts to prevent stunting is to improve the quality of mothers' knowledge through structured education. This can be done with the help of booklets and videos. This study was quasi-experimental with a pre and post-test design with a control group. The population in the study were all toddlers in the Nambo Public Health Center (PHC) working area in Kendari City in 2020 (230 toddlers). The number of samples was determined using the binominal proportions formula so that a sample was 60 toddler mothers. The data were analyzed using the paired T-Test test and Independent T-Test test. The results showed that education through booklets and videos in each group had a significant impact in increasing the knowledge of mothers under five about stunting and its prevention, with p-value= 0.000<=0.05, t-count= 5.396 and p-value= 0.000<=0.05, t-count= 10.441. While the follow-up test showed a significant difference in mothers' ability who were given booklet media and education through video media about stunting, its prevention was more effective in increasing the knowledge than education through booklets in the Nambo PHC working area, Kendari City, with p-value= 0.003<=0.05, t-count = 3.088. Booklet and video-based education were effective in increasing mothers' knowledge about stunting in toddlers and its prevention, but video-based teaching was more effective than booklet-based education.